Supporting Autistic Children's Participation in Research Studies: A Mixed-Methods Study of Familiarizing Autistic Children with A Humanoid Robot - Carly McGregor; Elisabeth von dem Hagen; Christopher Wallbridge; Jenna Dobbs; Caitlyn Svenson-Tree; Catherine RG Jones (Autism and Developmental Language Impairments)
It is important that autism research is inclusive and supports the participation of a wide range of autistic people. However, there has been limited research on how to make studies accessible for autistic participants. This mixed-methods study explored how to promote the comfort of autistic children in research, using the specific example of visiting a research lab and meeting a humanoid robot. In Phase 1, 14 parents of autistic children were interviewed about how their child could be made comfortable during a lab visit, including different approaches for familiarizing their child with the robot. In Phase 2, autistic children of the parents in Phase 1 ( n = 10) visited the lab and completed familiarization activities with a humanoid robot. The opinions of the children and their parents about the children's experiences were recorded. Using reflexive thematic analysis, five overarching themes reflected how to best support autistic child participants. These themes encompassed elements of particular relevance to robot studies but also many practices of general relevance to participating in research: (1) preparation is key, (2) consideration of environmental factors, (3) using familiarization, (4) a supportive and engaged researcher, and (5) individualized approaches. Based on our findings, we report preliminary and generalizable best-practice recommendations to support autistic children in a research setting and promote positive experiences.